Dorsal Nasal Skin Necrosis Following Rhinoplasty in Patients Treated with Topical Retinoids - Shyaka, Ian; Natasha, Natasha; Elangovan, Anjana; Ramasamy, Karthik (Indian Journal of Plastic Surgery, 2025)
Rhinoplasty is one of the most performed procedures by plastic surgeons worldwide, for both functional and cosmetic indications. The demand for aesthetic rhinoplasty in India has been on the rise over the past decade. Despite this rise in demand, rhinoplasty is still considered one of the most technically demanding procedures in plastic surgery. Complications following rhinoplasty are reported to be 4 to 18.8%, with dorsal skin necrosis being a rare complication that occurs in less than 1% cases. Out of a total of 244 rhinoplasties performed by a single surgeon at our institution, 2 cases of dorsal skin necrosis were encountered (0.8%). Currently, there is no literature describing dorsal skin necrosis following rhinoplasty among the Indian population. We present two patients who experienced dorsal nasal skin necrosis following open rhinoplasty while on topical 0.05% tretinoin treatment and highlight our management approach.
Keywords: rhinoplasty; dorsal nose skin necrosis; tretinoin